Temporal profiles of avalanches on networks - James P. Gleeson (Nature Portfolio, 2017)
Cascade propagation models represent a range of processes on networks, such as power-grid blackouts and epidemic outbreaks. Here the authors investigate temporal profiles of avalanches and show how nonsymmetric average avalanche shapes can occur at criticality.